Sosialisasi dan Pelatihan Pembuatan POC Berbasis Air Kelapa di Negeri Lesluru, Kecamatan Teon Nila Serua, Maluku Tengah - Atmaja, Nanda; Sufriadi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
Indonesia, as the largest producer of coconuts, holds the top position as the world's leading coconut producer. Lesluru is known as a region rich in natural resources, especially coconut plants, which are a major commodity for the local community and have great potential for utilizing the often-overlooked coconut water waste. The National Community Service Program PkM in Lesluru aims to educate farmers about processing coconut water waste into liquid organic fertilizer (POC). Through this program, the goal is to enhance the knowledge and skills of the community in processing coconut water waste into liquid organic fertilizer (POC). The methods applied include education, demonstration, and evaluation. Evaluation results show a significant increase in participants' knowledge of organic waste and its utilization, from 23% to 100%, as well as their practical ability to make POC, which increased from 0% to 92.3%. The application of liquid organic fertilizer is expected to support sustainable agriculture, improve agricultural yields, and reduce the negative environmental impact of coconut water waste. These findings highlight the importance of community-based training to utilize local resources, which can contribute to the economic well-being of the community and environmental sustainability.